Intussusception among Japanese children: an epidemiologic study using an administrative database - Takeuchi Masato; Osamura Toshio; Yasunaga Hideo; Horiguchi Hiromasa; Hashimoto Hideki; Matsuda Shinya (BMC, 2012)
Abstract Background The epidemiology of intussusception, including its incidence, can vary between different countries. The aim of this study was to describe the epidemiology of childhood intussusception in Japan using data from a nationwide inpatient database. Methods We screened the database for eligible cases ≤ 18 years of age, who were coded with a discharge diagnosis of intussusception (International Classification of Diseases, 10th revision: K-561) between July to December in 2007 and 2008. We then selected cases according to Level 1 of the diagnostic certainty criteria developed by the Brighton Collaboration Intussusception Working Group. We examined the demographics, management, and outcomes of cases, and estimated the incidence of intussusception. Results We identified 2,427 cases of intussusception. There were an estimated 2,000 cases of infantile intussusception annually in Japan, an incidence of 180-190 cases per 100,000 infants. The median age at diagnosis was 17 months, and two-thirds of the patients were male. Treatment with an enema was successful in 93.0% of cases (2255/2427). The remainder required surgery. Secondary cases accounted for 3.1% (76/2427). Median length of hospital stay was 3 days. Of the 2,427 cases, we found 2 fatal cases associated with intussusception. Conclusions This is currently the largest survey of childhood intussusception in Asia using a standardized case definition. Our results provide an estimate of the baseline risk of intussusception in Japan, and it is higher than the risk observed in other countries.